Pulmonary synovial sarcoma: A case series and review of literature - Peter, Amrutha; Shukla, Amarendra Kumar; Gupta, Manish Kumar; Patel, Vikas; Kumar, Vijaya; Arya, Veerendra; Tiwari, Pawan; Bhargava, Jitendra Kishore (Asian Journal of Medical Sciences, 2022)
Synovial sarcoma is a rare malignant mesenchymal tumor that can develop at any anatomic site. Pulmonary sarcomas constitute 0.1–0.5% of all primary lung malignancies. Primary pulmonary synovial sarcoma is highly uncommon. Most of the patients present with large intrathoracic masses with complaints of cough, chest pain, shortness of breath, or hemoptysis. Multimodality treatment in the form of wide excision, chemotherapy, and radiotherapy is the mainstay of therapy. Synovial sarcoma is considered a high-grade tumor with a poor prognosis. We hereby present three cases of histologically proven synovial sarcoma with predominantly pulmonary involvement, along with their management and in hospital outcome.